Chronic pelvic inflammatory disease and fertility - Pacheco, José (2015)
Objective: To review the frequence and modality of presentation of chronic pelvic inflammatory disease in infertile patients. Design: retrospective observational transversal preliminarity clinical study in infertile women. Material: 121 women subjected to laparoscopy or laparotomy at the Human Reproduction Service of Edgardo Rebagliati Martins National Hospital, PPSI, in one year. Results: Chronic pelvic inflammatoy disease was found in 82 cases (68%), tubal obstruction in 59 (72%), adhesions in 47 (57%) chronic salpingitis in 9, hydrosalpinx in 15(18%) and phymosis in 3 cases (4%). We performed lysis of adhesions in 35 cases, lysis of fimbria in 33, salpingofimbriolysis in 45, fimbrionestomy in 10, salpingofimbriovariolysis in 6, tubal reimplant in 4 and other modalities in 17. Salpingoneostomy was performed for ectopic pregnacy in 3 cases. Conclusion: Chronic pelvic inflammatory disease is rather frequent in infertile women subjected to laparosocpy or laparotomy at our Service, originating difficulty in the management of this type of infertility problem.